Towards human organ generation using interspecies blastocyst complementation: Challenges and perspectives for therapy - Sarmah, Hemanta; Sawada, Anri; Hwang, Youngmin; Miura, Akihiro; Shimamura, Yuko; Tanaka, Junichi; Yamada, Kazuhiko; Mori, Munemasa (Frontiers in Cell and Developmental Biology, 2023)
Millions of people suffer from end-stage refractory diseases. The ideal treatment option for terminally ill patients is organ transplantation. However, donor organs are in short supply, and most patients sadly die waiting for a donor organ. There is an unmet need to generate patient-derived organs, and many attempts have been made for several decades. However, no technology has achieved functional organ generation that can sustain long-term without immunosuppression. In this regard, leveraging xenogeneic organ sources, such as gene-manipulated swine, hold great promise. Of note, the latest preclinical trial of renal implantation from swine to a brain-dead human patient has unlocked a new paradigm for evaluating xeno-organs. As an emerging field, the generation of chimeric human organ bioengineering via blastocyst complementation, and use of bio-scaffolds, is also encouraging. However, all these organ transplantation technologies require overcoming the interspecies barrier, including immune and non-immune-mediated rejection. To take this field of human organ generation and transplantation to the next step, we reviewed current emerging organ generation technologies and the associated efficiency of chimera formation in human cells from the standpoint of developmental biology.